The DESIGN OF FIBER METAL LAMINATE AS A BODY MATERIAL WITH CARBON FIBER METHOD - Muhammad Juliansyah Winarto; Lalu Saefullah; Willem Loe Mau (Pustaka Poltekad, 2021)
The combat vehicles that Indonesia Army belong to most of the materials are steel, for example the armored vehicle anoa 6x6. Steel material is used as a fire protection on the vehicle, it will greatly affect the performance of the vehicle. It is caused the steel material has a high density, which is around 7750 kg/m3to 8050 kg/m3. So, with a large enough volume of the vehicle body, it will increase the burden of the vehicle. As well as the engine load will increase, and more power is needed to be able to move the vehicle. Seeing these problems, it is necessary to have a research or study on alternative materials to replace the body of a combat vehicle that can withstand fire from opposing weapons that cause personnel to be injured. In this study, experimental and simulation methods were used using the ansys application to analyze the strength of the composite material in the form of an aluminum layer that had been treated to increase the hardness value. Furthermore, it is coated with a composite material using a carbon fiber matrix of epoxy, HGM and polyurethane. The coating material is called Fiber Metal Laminate (FML), so the material used has a lighter density, the load received by the vehicle engine is lighter, and the performance of the vehicle will be more effective and efficient.